PENGEMBANGAN E-MODUL MENGGUNAKAN CANVA MATERI ORGAN PENCERNAAN MANUSIA DAN FUNGSINYA - Annisa Permata Sari; Lina Novita; Nur Hikmah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Development of E-Modules Using Canva Material for the Human Digestive Organs and Their Functions. This research uses the type of R&D (research and development) research. The purpose of this research is for e-module developers using Canva material for the human digestive organs and their functions. The subjects of this study were fifth grade students at SDN Margajaya 3 Bogor City with a total of 35 students using ADDIE (Analaysis, Design, Development, Implementation, Evaluation). The progress of information and communication technology in the world of education is developing very well. Then do a limited trial to the respondents who have been determined. The validation results from media experts with a percentage of 91.25%, linguists with a percentage of 94.28%, material experts 1 with a percentage of 92%, and material experts 2 with a percentage of 100%. So thus the development of e-modules uses Canva material for the human digestive organs and their functions are "Very Eligible" and "Very Good" for use in the process of teaching and learning activities in schools, easy to understand, interesting, and fun.